Faktor risiko untuk fungsi hip yang buruk pada pasien dengan patah tulang kolum femur pasca hemiarthroplasti bipolar tiga bulan pasca operasi - Soehartono Hadi Pranata; Putu Astawa; I Wayan Suryanto Dusak (DiscoverSys Inc., 2020)
Introduction. As one of the frequent problems globally, fractures of the column femur may cause morbidity and mortality if not well-treated. The most common treatment for hip fracture is bipolar hemiarthroplasty. Hemiarthroplasty generally has good results, but with increasing patient age, implant function deteriorates. Through this research, the authors were interested in investigating the factors that may contribute to the functional outcome of bipolar hemiarthroplasty procedure, including Leg Length Discrepancy (LLD), osteoporosis, the diameter of the femoral head, stem malposition, and implant loosening.Methods. This is a case-control study. The case group was patients with Harris Hip Score (HHS) < 70 (poor hip function), while the control group was patients with HHS > 70. X-ray examination was performed to evaluate for the LLD, stem malposition, osteoporosis, femoral head diameter, and implant loosening three months after surgery. The result was tabulated in 2x2 tables, then descriptive and inferential analysis was conducted.Results. Chi-square tests for LLD, osteoporosis and femoral head diameter yielded p = 0.012, p = 0.026, and p = 0.002 respectively, showing significant differences in HHS at three months after bipolar hemiarthroplasty surgery (p <0.05). While the chi-square test for implant loosening and stem malposition resulted in p = 0.469 and p = 0.115, neither of these showed significant differences between groups (p> 0.05).Conclusion. Differences in leg length (LLD), osteoporosis, and diameter of the femoral head were risk factors for the poor functional outcome (HHS <70) at three months after surgery in patients who underwent bipolar hemiarthroplasty due to fracture of the femoral column. Meanwhile, the stem malposition and loosening of the implant have not been shown any association with HHS <70. Pendahuluan. Sebagai salah satu masalah yang sering terjadi secara global, patah tulang kolum femur dapat menyebabkan morbiditas dan mortalitas jika tidak diobati dengan baik. Pengobatan yang paling umum untuk patah tulang panggul adalah hemiarthroplasti bipolar (bipolar hemiarthroplasty). Hemiarthroplasti umumnya memiliki hasil yang baik, tetapi dengan bertambahnya usia pasien, fungsi implan memburuk. Melalui penelitian ini, penulis tertarik untuk menyelidiki berbagai faktor yang dapat berkontribusi terhadap hasil fungsional setelah prosedur hemiarthroplasti bipolar, termasuk perbedaan panjang tungkai (leg length discrepancy / LLD), osteoporosis, besar diameter kepala femur, malposisi stem, dan pelonggaran implan.Metode. Studi menggunakan desain kasus-kontrol. Kelompok kasus adalah pasien dengan Harris Hip Score (HHS) < 70 (luaran fungsional buruk), sedangkan kelompok kontrol adalah pasien dengan HHS > 70. Pemeriksaan foto polos dilakukan untuk melihat LLD, malposisi stem, osteoporosis, diameter kepala femur, dan pelonggaran implan. Data disusun dalam bentuk tabulasi silang kemudian analisis deskriptif dan inferensial.Hasil. Uji chi-square untuk LLD, osteoporosis dan diameter kepala femur menghasilkan nilai p = 0,012, p = 0,026, dan p = 0,002 berturut-turut, menunjukkan perbedaan yang bermakna dalam hal HHS pada tiga bulan pasca operasi pada pasien dengan fraktur kolum femur setelah hemiarthroplasti bipolar (p < 0,05). Sementara uji chi-square untuk pelonggaran dari implan dan malposisi stem menghasilkan nilai p = 0,469 dan p = 0,115, keduanya tidak menunjukan perbedaan bermakna antar kelompok (p > 0,05).Simpulan. Perbedaan panjang tungkai (LLD), osteoporosis, dan besar diameter kepala dari tulang femur merupakan faktor risiko untuk luaran fungsional yang buruk (HHS < 70) setelah hemiarthroplasti bipolar setidaknya tiga bulan setelah pembedahan pada pasien dengan fraktur kolum dari tulang femur. Faktor malposisi stem dan pelonggaran dari implant belum terbukti menjadi faktor risiko.